Exploiting non-orthogonal multiple access in device-to-device communication - Sang Hoon Lee; Soo Young Shin (Institute of Advanced Engineering and Science, 2021)
This paper proposes an uplink non-orthogonal multiple access (NOMA) system with device-to-device (D2D) communication, enabling NOMA users to communicate with other users/devices using D2D communication to improve the system capacity. In the NOMA-D2D system, two cellular users communicated with the BS using uplink NOMA, and two cellular users simultaneously communicated with the D2D users using downlink NOMA. Closed-form solutions for the ergodic sum capacity of the proposed system are derived analytically. The analytical results are validated via simulations and they are compared with the results obtained from conventional schemes. The comparison shows that, in scenarios where efficient interference cancellation can be achieved, the proposed NOMA system with the D2D model can achieve higher capacity gains than conventional benchmark schemes. When dB, NOMA-D2D achieves capacity gains of 192.2% and 157.5% over the conventional OMA and the time-sharing-based NOMA, respectively.